Success Factors of Social Science Education Students in the Personality Development Course at Tanjungpura University - M Zainul Hafizi (International Journal of Applied Educational Research (IJAER), 2024)
This study analyzes the factors that influence the academic success of students in the course of Social Personality Development in the Social Science Education Program at the Faculty of Teacher Training and Education, Tanjungpura University. A quantitative descriptive method was used with a sample of 33 students. The data includes class activity grades, assignments, Midterm Exams (UTS), Final Exams (UAS), and final grades. The results show that class activity has the strongest correlation with the final grade (r = 0.72), followed by assignments (r = 0.68), UTS (r = 0.64), and UAS (r = 0.62). The majority of students (91.18%) obtained an A grade. In conclusion, class activity and assignments play a significant role in students' academic success.